2020
DOI: 10.1080/13636820.2020.1771087
|View full text |Cite
|
Sign up to set email alerts
|

From hospitality classrooms to successful careers: an appraisal of Australian hospitality higher education

Abstract: This work has not previously been submitted for a degree or diploma in any university. To the best of my knowledge and belief, the thesis contains no material previously published or written by another person except where due reference is made in the thesis itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 218 publications
0
1
0
Order By: Relevance
“…The targeted sample size was not reached, which is common in studies involving hotel managers. Fraser (2017) mentions that, due to the demanding nature of their work, hotel managers are known to be reluctant to participate in research. Although this is a contributing factor in this study, the researcher identified other possible reasons for the small sample size, namely (a) COVID-19 restrictions, (b) low staff morale, and (c) hesitancy to participate in any form of research.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…The targeted sample size was not reached, which is common in studies involving hotel managers. Fraser (2017) mentions that, due to the demanding nature of their work, hotel managers are known to be reluctant to participate in research. Although this is a contributing factor in this study, the researcher identified other possible reasons for the small sample size, namely (a) COVID-19 restrictions, (b) low staff morale, and (c) hesitancy to participate in any form of research.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%